Progress on Crystal Growth of Two-Dimensional Semiconductors for Optoelectronic Applications - Bingqi Sun; Jing Xu; Min Zhang; Longfei He; Hao Zhu; Lin Chen; Qingqing Sun; David Wei Zhang (Crystals, 2018)
Two-dimensional (2D) semiconductors are thought to belong to the most promising candidates for future nanoelectronic applications, due to their unique advantages and capability in continuing the downscaling of complementary metal–oxide–semiconductor (CMOS) devices while retaining decent mobility. Recently, optoelectronic devices based on novel synthetic 2D semiconductors have been reported, exhibiting comparable performance to the traditional solid-state devices. This review briefly describes the development of the growth of 2D crystals for applications in optoelectronics, including photodetectors, light-emitting diodes (LEDs), and solar cells. Such atomically thin materials with promising optoelectronic properties are very attractive for future advanced transparent optoelectronics as well as flexible and wearable/portable electronic devices.